Cooperative game-based profit allocation for joint distribution alliance under online shopping environment: A case in Southwest China. Issue 2 (8th April 2019) - Li, Longxiao; Wang, Xu; Lin, Yun; Zhou, Fuli; Chen, Shan
Abstract : Purpose: In the context of sharing economy and online shopping, establishing a stable urban joint distribution alliance (JDA) is extremely necessary for the entire logistics service market. The purpose of this paper is to rationally allocate the profits and determine the most stable allocation scheme for the urban JDA as well as provide a direction for cooperation between express enterprises and lead managers to pay more attention to the comprehensive performance. Design/methodology/approach: Cooperative game-based methodologies including the proportion method, the core theory, nucleolus and Shapley value have been employed. Four criteria consisting of enterprise operation, customer satisfaction, environmental sustainability and information technology have been incorporated into Shapley value for improvement. Findings: This paper reveals that express enterprises in logistics service market can achieve more benefit from JDA than those who operate separately. Among proposed profit allocation schemes, improved Shapley value scheme shows more rationality by considering partners' asymmetric contribution. Besides, a stable alliance can be always ensured with partners' lower propensity to disrupt and relatively balanced negotiation power under improved Shapley value scheme. Originality/value: This paper makes a few attempts to contribute to the literature on the improvement of Shapley value and applies the concept of "propensity to disrupt" into the field of logistics. Besides, this paper provides various profit allocation schemes and incorporates influencing factors into Shapley value for an improvement thus helping policy-makers make better-informed decisions on urban distribution. Additionally, a case study based on urban express enterprises in Southwest China has been conducted to verify the proposed profit allocation schemes.